2017
DOI: 10.3847/1538-4357/aa8a6c
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Correlation between Star Formation Activity and Molecular Gas Properties Across Environments

Abstract: We present the molecular gas mass fraction (f H2 ) and star-formation efficiency (SFE) of local galaxies on the basis of our new CO(J = 1 − 0) observations with the Nobeyama 45m radio telescope, combined with the COLDGASS galaxy catalog, as a function of galaxy environment defined as the local number density of galaxies measured with SDSS DR7 spectroscopic data. Our sample covers a wide range in the stellar mass and SFR, and covers wide environmental range over two orders of magnitude. This allows us to conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…We also found no evidence for a different depletion timescale in denser environments than the field to z ∼ 3.5 consistent with e.g. Koyama et al (2017) at z ∼ 0 and Noble et al (2017) at z ∼ 1.6. However, some studies have suggested that denser environments accelerate (decelerate) the consumption of molecular gas, leading to a shorter (longer) τ in denser regions (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also found no evidence for a different depletion timescale in denser environments than the field to z ∼ 3.5 consistent with e.g. Koyama et al (2017) at z ∼ 0 and Noble et al (2017) at z ∼ 1.6. However, some studies have suggested that denser environments accelerate (decelerate) the consumption of molecular gas, leading to a shorter (longer) τ in denser regions (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by the lack of environmental effects on the molecular gas content of galaxies as seen in some studies (e.g. ; Kenney & Young 1989;Koyama et al 2017). However, others find lower (e.g.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We performed data reduction by following the procedure described in Koyama et al (2017) using the NEW-STAR software developed by NRO based on the Astronomical Image Processing System (AIPS) package. We only used the data with wind velocities of < 5 m s −1 , pointing accuracies with <5 , system noise temperature (T sys ) with <300 K, and the data with the rms noise temperature of T rms < 0.045 K in the T mb scale at a velocity resolution of 200 km s −1 to exclude bad baseline spectra.…”
Section: Observation and Data Reductionmentioning
confidence: 99%
“…Gas fraction and star formation efficiency of galaxies can be responsible for deviation from the main sequence in the plane of SFR-M stellar , in the sense that starburst (passive) galaxies tend to have larger (smaller) gas fraction and/or higher (lower) efficiency of star formation (Saintonge et al 2012(Saintonge et al , 2016(Saintonge et al , 2017Sargent et al 2014). On the other hand, as long as we focus on star-forming galaxies, an environment where galaxies reside do not have a strong impact on the star-forming main sequence and the relationship between gas reservoirs and star-formation activity (Peng et al 2010;Koyama et al 2017). These observational studies may suggest that star formation activity in most of galaxies is governed not by external process such as galaxy interaction but by internal factors such as gas reservoir.…”
mentioning
confidence: 99%